2016
DOI: 10.1016/j.nicl.2016.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions in cortico-subcortical covariance networks associated with anxiety in new-onset childhood epilepsy

Abstract: Anxiety disorders represent a prevalent psychiatric comorbidity in both adults and children with epilepsy for which the etiology remains controversial. Neurobiological contributions have been suggested, but only limited evidence suggests abnormal brain volumes particularly in children with epilepsy and anxiety. Since the brain develops in an organized fashion, covariance analyses between different brain regions can be investigated as a network and analyzed using graph theory methods. We examined 46 healthy chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…Our fMRI findings should also be interpreted in the context of previously shown structural brain changes in patients with ECTS, including abnormal cortical morphology and white matter development in fronto-parietal regions involved in WM, and reduced structural connectivity in sensorimotor and language areas ( Besseling et al, 2013a , Ciumas et al, 2014 , Garcia-Ramos et al, 2015 , Garcia-Ramos et al, 2016 , Hutchinson et al, 2010 , Lin et al, 2012 , Pardoe et al, 2013 , Tosun et al, 2011 , Widjaja et al, 2013 ).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our fMRI findings should also be interpreted in the context of previously shown structural brain changes in patients with ECTS, including abnormal cortical morphology and white matter development in fronto-parietal regions involved in WM, and reduced structural connectivity in sensorimotor and language areas ( Besseling et al, 2013a , Ciumas et al, 2014 , Garcia-Ramos et al, 2015 , Garcia-Ramos et al, 2016 , Hutchinson et al, 2010 , Lin et al, 2012 , Pardoe et al, 2013 , Tosun et al, 2011 , Widjaja et al, 2013 ).…”
Section: Discussionmentioning
confidence: 63%
“…ECTS is often associated with neuropsychological deficits believed to reflect the interference between the epileptic focus and other brain regions during development. The cognitive dysfunctions observed in children with ECTS, including altered WM, have been linked to an abnormal developmental trajectory of brain structures, particularly those affected by epilepsy ( Besseling et al, 2013a , Bourel-Ponchel et al, 2019 , Ciumas et al, 2014 , Garcia-Ramos et al, 2015 , Garcia-Ramos et al, 2016 , Hutchinson et al, 2010 , Lin et al, 2012 , Tosun et al, 2011 , Widjaja et al, 2013 ). Task-based functional neuroimaging studies have shown that ECTS is associated with: 1) reduced activity during verbal generation task within language-related regions, in particular over the anterior language network ( Lillywhite et al, 2009 ), 2) a wider network recruitment during sentence reading comprehension ( Malfait et al, 2015 ), 3) reduced language laterality index, with more bilateral and right-hemispheric activations ( Datta et al, 2013 ) , 4) remodelling of language networks ( Vannest et al, 2013 ) and 5) altered responses to fearful stimuli ( Ciumas et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The global measures investigated included global efficiency, transitivity, community structure, and modularity index (Q), using modularity Louvain algorithm, and were calculated over a range of hybrid thresholds (0.15–0.35; 0.02 intervals). These measures have been thoroughly described in previous work ( Garcia-Ramos et al, 2016 ). Global efficiency examines network integration ( Wang et al, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…These findings suggested that the right hemisphere might have a greater influence on emotional networks and play a greater role in psychiatric commobidites. In addition, a graph theory analysis based on T1-weighted 3D spoiled gradient recall (SPGR) showed large scale disruptions in cortical and subcortical brain regions in children with recent onset epilepsy and anxiety [72]. Influence in the network is not necessarily local but potentially influencing other more distant regions [71].…”
Section: Abnormal Network and Neurocognitive And Psychiatric Comorbimentioning
confidence: 99%